The Qur'anic Learning Based on Islamic Eco-Theology at Pesantren - Karman Karman; Rosihon Anwar; Lukman Hakim (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2023)
The research investigates the intersection of Qur'anic learning, eco-theology, and environmental transformation at the Biharul Ulum Agroecology pesantren (BUAP) in Bogor. Recognizing that environmental issues stem largely from human behavior, the study explores how perspectives derived from the holy book influence individuals. Employing moral theory and liberation theology, the research adopts a qualitative and ethnographic approach to reveal the impact of theology-based Al-Quran learning on environmental practices at pesantren. The findings illustrate that eco-theology-based learning has sparked a notable environmental transformation, shielding the community from ecological crises. This transformation unfolds through a multifaceted process: communal dialogues addressing local challenges, rigorous study of the Quran under the guidance of kyai (Islamic scholars), and subsequent environmental conservation initiatives spearheaded by pesantren. The amalgamation of religious teachings with practical actions has not only mitigated environmental crises but has also alleviated social challenges. BUAP serves as a catalyst for positive change and demonstrates the potential of Qur'anic learning to inspire environmentally conscious behavior. This research contributes to understanding the role of Islamic education in fostering eco-conscious attitudes and offers insights into the synergy between religious teachings and environmental stewardship for the betterment of society.